(untitled) (Journal of Parents and Teachers, 1995)
The importance of patience and emotional management in the education and upbringing of children, highlighting the need for attention and admiration for their development. Positive methods of influencing young people’s behavior are mentioned, as well as the relevance of communication and understanding between parents and children.